Asuhan Kebidanan Pada Ibu Nifas Post SC Dengan Nyeri Luka Jahitan Di Wilayah Kerja Rumah Sakit Amelia Kabupaten Kediri - Diah Ayu Setiyowati; Estin Gita Maringga (Jurnal Kebidanan Manna, 2022)
Sectio caesaria (SC) is a process of delivery or surgery through an incision in the abdominal wall and the front of the uterus to deliver the fetus. The method used case study. The sample in this study is a single unit, namely Ny.S G2P1001 post SC. Data collection was obtained by interview, physical examination, observation, medical record acquisition and patient medical record reports. The results of the assessment carried out in this patient were TTV within normal limits, post-SC pain was found on the 2nd postpartum day. After evaluating the midwifery measures given for 4 visits, the results showed that the patient's pain was resolved on a pain scale of 1-4, there were no signs of infection, the patient was able to work independently, and the patient rested. Midwifery care given to Mrs. S post SC with suture pain has been able to provide comfort and minimize complications for postpartum mothers in facing the wound healing phase of post SC suture wounds.